1980
DOI: 10.1002/j.2050-0416.1980.tb03951.x
|View full text |Cite
|
Sign up to set email alerts
|

PECTINATUS, A NEW GENUS OF BACTERIA CAPABLE OF GROWTH IN HOPPED BEER

Abstract: The properties of a new bacterial genus that is capable of growth in hopped beer are described. The organism is an anaerobic gram-negative, non-spore forming mesophilic rod with flagella emanating from one side of the cell body. It produces a considerable amount of H2S and high turbidity when grown in packaged beer. No alcohol was produced from glucose unlike the genus Zymomonas. The guanine-plus-cytosine content of the deoxyribonucleic acid is 39*8 mol %. The physical and biochemical characteristics of this o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
6

Year Published

1981
1981
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 5 publications
0
20
0
6
Order By: Relevance
“…Pectinatus is an anaerobic contaminant of unpasteurized beer that has been isolated since the 1970s 88,89 . This strictly anaerobic bacterium that stains Gram-negative is affiliated to the Sporomusa sub-branch of the class Clostridia in the phylum Firmicutes 66 .…”
Section: Current Taxonomy Of Pectinatus and Megasphaeramentioning
confidence: 99%
See 1 more Smart Citation
“…Pectinatus is an anaerobic contaminant of unpasteurized beer that has been isolated since the 1970s 88,89 . This strictly anaerobic bacterium that stains Gram-negative is affiliated to the Sporomusa sub-branch of the class Clostridia in the phylum Firmicutes 66 .…”
Section: Current Taxonomy Of Pectinatus and Megasphaeramentioning
confidence: 99%
“…Most of the strains described and characterized to date have been almost exclusively isolated from beer. However, Pectinatus has sporadically been found in lubrication oil mixed with beer, drainage and water pipe systems, air of the filling hall and the filling machine, as well as on the floor of the filling hall, in condensed water on the ceiling, in chain lubricants and in the steeping water of malt before milling 11,43,61,89,130 . Other studies further showed that Pectinatus is found in conveyors, sewers, supporting structures of filler, and loose tiles or cracks of damaged floors and walls in breweries 8,100 .…”
Section: Current Taxonomy Of Pectinatus and Megasphaeramentioning
confidence: 99%
“…Pectinatus spp. produce considerable amounts of acetic and propionic acid as well as acetoin in wort and packaged beers 110,177 . Beer spoilage by Pectinatus spp.…”
Section: Fermentationmentioning
confidence: 99%
“…Beer spoilage by Pectinatus spp. is characterised by extensive turbidity and an offensive 'rotten egg' smell as a result of the production of hydrogen sulphide and methyl mercaptan 72,109,110 .…”
Section: Fermentationmentioning
confidence: 99%
“…have been reported mainly from spoiled beer and pitching yeast 16 . They have also been isolated from drainage and water pipe systems of beer filling halls, parts of filling machines and the air and floor of filling halls, condensed water on ceilings, loose tiles and in cracks of damaged floors 3,7,32,35 . Plate counting and enrichment remain the principal methods for detection of microbial contamination in breweries during the brewing process and in final products 8 .…”
Section: Introductionmentioning
confidence: 99%